Analyzing the relationship between consumers’ and entrepreneurs’ food waste and sustainable development using a bibliometric approach - Kostakis, Ioannis; Papadaki, Stamatina; Malindretos, George (Frontiers in Sustainability, 2024)
The present study investigates the relationship between food waste and sustainable development, aiming to reveal contextual insights and present novel findings regarding the pivotal importance of waste and environmental strategies toward a circular economy. This research represents an effort to delineate methodological and thematic contributions, thoroughly analyze key themes, examine co-citation patterns, assess collaboration among countries, and identify current knowledge gaps in the literature. As waste management takes precedence within the framework of sustainable development goals, policymakers, and academia will better understand how effective food waste management can contribute to environmental sustainability. Methodologically, we employ systematic review, employing the PRISMA approach, analyzing 761 final papers, and investigating the relationship between food waste and sustainable development. We delve deeper to reveal contextual insights and present empirical findings that underscore the critical role of food waste in the economy and environment. Furthermore, guided by the identified knowledge gaps, we illuminate potential future research avenues that hold immense promise for advancing our understanding of food waste and its impact on sustainable development.